Induction of p53-mediated apoptosis by azacitidine in patient-derived xenograft follicular helper T-cell lymphoma model - Crochet, Gamze Tari; Ari-Yuka, Selcen; Fischer, Anja; Chour, Mohamed; Claudel, Alexis; Sako, Nouhoum; Robe, Cyrielle; Naudet, Julie; Gonon, Alexis; Mboumba, Diana Laure; Ortonne, Nicolas; Alcazer, Vincent; et al. (SPRINGERNATURE, 2025)
Follicular helper T-cell lymphoma (TFHL) is the most common non-cutaneous T-cell lymphoma in the Western world and is associated with a poor prognosis. Neoplastic cells rely heavily on the tumor microenvironment, demonstrated by the absence of TFHL-derived cell lines, which hinders therapeutic progress. To overcome this limitation, we developed and characterized patient-derived xenograft TFHL (TFHL-PDXs). Fifteen TFHLs were implanted into immunodeficient mice, generating nine PDXs. The tumor microenvironment was detected in the first passage but progressively disappeared in subsequent passages. TET2 mutations persisted in all cases and TFHL-specific mutations were observed in most. The models were treated with azacitidine and patient sensitivity was fully recapitulated. To elucidate the mechanism of action of azacitidine, we analyzed the differences in DNA methylation and gene expression in six TFHL-PDX models. Global DNA hypomethylation occurred in azacitidine-treated cells in drug-sensitive models but not in the resistant ones. DNA hypomethylation was associated with global upregulation of gene expression, including that of various cancer-related pathways, suggestive of p53-pathway-mediated cytotoxicity. Overall, the PDXs recapitulated TFHL features and exhibited sensitivity to azacitidine. They also made it possible to decipher the mechanism responsible for the effect of azacitidine, revealing the activation of p53-mediated apoptosis associated with DNA hypomethylation.
Keywords: MUTATIONS; TET2; RHOA; Oncology; Hematology